Theological Anthropology of the Heart in Dilexit Nos: Its Relevance to the Contemporary Crisis of Empathy - Bertolomeus N.A.P. Ngita; Petrus Bagul; Higianes Indro Pandego; Antonius Moa (SEAN Institute, 2026)
This article examines the theological anthropology of the heart in Pope Francis' Encyclical Dilexit Nos and its relevance to the contemporary crisis of empathy. Amid the growing influence of individualism, pragmatism, and the erosion of authentic human relationships, the study argues that this crisis is fundamentally anthropological, rooted in humanity's loss of orientation toward God as the source of love and communion. Employing qualitative library research within the framework of systematic dogmatic theology, the study analyzes Sacred Scripture, Sacred Tradition, the Magisterium of the Church—particularly the Catechism of the Catholic Church—together with the Encyclical Dilexit Nos. The findings demonstrate that, according to Catholic teaching, the heart is the deepest center of the human person, where intellect, conscience, freedom, will, and love are integrated in communion with God. In continuity with Scripture, Tradition, and the Magisterium, Dilexit Nos presents the Heart of Christ as the fullest revelation of divine love and as the anthropological paradigm for the renewal of the human person. Consequently, the transformation of the heart becomes the foundation of personal conversion, ecclesial communion, and social solidarity. This study concludes that Dilexit Nos represents the contemporary maturation of the Church's doctrinal reflection on the theological anthropology of the heart and offers a coherent dogmatic framework for responding to the crisis of empathy in the contemporary world.